PENGARUH ORIENTASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (Survei pada Pegawai Kantor Pelayanan Pajak Pajak Pratama Sukoharjo) - Fitri Wahyuningsih; Alwi Suddin; Suprayitno Suprayitno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This study aims to analyze the significance of the influence of work orientation and organizational culture on employee performance with motivation as a moderating variable. This type of research is a survey of the Pratama Tax Service Office Staff Sukoharjo. The type of data is by collecting qualitative data and quantitative data. Data sources used are primary and secondary data sources. The study population was 118 employees with a sample of 59 people with a proportional cluster random sampling technique. Data collection techniques using questionnaires. The data analysis technique used is instrument test, classic assumption test, multiple linear regression, t test, F test, coefficient of determination and absolute difference test. The results showed that work orientation had a positive and significant effect, organizational culture had a negative effect and was not significant, motivation was influential and significant while motivation did not moderate work orientation and organizational culture.